Iran and the Arab Spring: Between Expectations and Disillusion - Henner Fürtig (German Institute of Global and Area Studies (GIGA), 2013)
The 1979 Iranian Revolution undoubtedly belongs to the great revolutions of modern times - all of which were characterized by universalistic efforts and the claim to have set new social, political and cultural norms with global validity. In this sense, the Iranian revolutionaries felt the obligation to actively reintroduce Islam as a revelation for the whole world, not only for Muslims. Yet, they soon became aware that most Muslims viewed their export strategy as either an attempt to enforce Shiism, or - even worse - to conceal mere national megalomania. Therefore, the current leadership argues that the revolution should no longer be exported actively, but that Iran should serve as an example. Consequently, Supreme Leader Khamenei called the events of the Arab Spring a natural enlargement of Iran's Islamic revolution of 1979 and credited his country for being the catalyst of this Islamic awakening. The present article will analyze selected regional reactions to the Islamic awakening concept, which did not altogether meet Iranian expectations.
Keywords: 300; Arab Spring; Iran; political Islam; Middle East; regional system